The CPEC supply web framework in context of modern manufacturing - Bugvi, Salman Abubakar; Hameed, Khurram; Hussain, Amjad; Tabassum, Salim Abid (Penerbit Universiti Kebangsaan Malaysia, 2021)
There is a need to understand and integrate the technologies and concepts of the 4th industrial revolution (Industry 4.0), supply chain management, modern manufacturing and the opportunities provided by the logistic and development programs of Belt Road Initiative (BRI) and China Pakistan Economic Corridor (CPEC). The knowledge of multiple fields such as industry 4.0, supply chain management, logistic supply chain management and CPEC project plans have been synthesized. An attempt has been made to model a future state created through CPEC facilities and initiatives. A model framework is presented based on the core infrastructure of CPEC projects, which will push Pakistan towards industrialization through utilizing modern manufacturing techniques and establishment of supply web. The CPEC supply web model proposes to create high quality, mass customized products from raw material and parts to be supplied from local and nearby regions through efficient logistic pathway of CPEC and BRI. A supply chain operational reference (SCOR) model has also been developed for an insight into the scenario. It is important for investors, trade associations, businessmen and policy makers to understand the population, market, and economic dynamics along with modern manufacturing trends to create smart factories and supply chains in context of CPEC. The lessons learned from the planning, development and application of the solutions presented by CPEC can be utilized by other regions and countries depending on their relevant unique geostrategic and economic perspectives.